Perancangan Jaringan Sensor Terdistribusi untuk Pengaturan Suhu, Kelembaban dan Intensitas Cahaya - Bimo Ananto Pamungkas; Adian Fatchur Rochim; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2013)
This paper contains distributed sensor system design for temperature, air humidity, and light intensity monitoring in greenhouse based Arduino Uno board. System contains 2 sensor-actuator nodes, and 1 controller node connected to Ethernet network through Ethernet Shield board. Sensor-actuator node with DHT 11 sensor works for taking environment informations such as temperature, air humidity, and light intensity, runs actuation in the form of emulating LED lights; and communicates with controller node which will process data using serial wire as a communication tool between nodes. Monitoring datas and user control interface is provided by controller node which can be accessed online in web browser. The system ability for monitoring environment in greenhouse and online access of environmental data generates controllable and automatic monitoring and management of plants.